Effect of Strategic Orientation on Firm Performance : A Mediation Analysis - Goyal, Arpita; Mishra, Uma Sankar; Mishra, Satyakama; Ray, Manidatta (Prabandhan: Indian Journal of Management, 2024)
Purpose : The purpose of this study was to investigate the notion that the market environment (ME) functions as a mediator between strategic orientation (SO) and firm performance. Methodology : A systematic questionnaire was used to get information from a sample of 220 SME managers and owners in Rajasthan, India. Structural equation modeling was utilized to test the hypotheses. Findings : The results demonstrated that the direct influence of SO improves the performance of the organization. The ME partially mediated the impacts of SO on company performance. Practical Implications : The results of the study demonstrated that successful business owners focus on their customers, seek out and seize new markets, and are committed to developing and implementing innovative ideas. They also need to use technology in their products and procedures. Originality : This study advanced our understanding of the effects of different SOs on FP by utilizing the ME analysis techniques.